Fluid drawing printing 3D conductive structures for flexible circuit manufacturing - Yikang Li; Dazhi Wang; Yiwen Feng; Xiangji Chen; Xu Chen; Chang Liu; Yanteng Li; Liujia Suo; Ran Zhang; Xiaopeng Zhang; Ben Liu; Fengshu Wang; et al. (Microsystems & Nanoengineering)
Abstract Three-dimensional (3D) conductive structures significantly reduce flexible circuit complexity and enhance circuit integration. Direct extrusion printing technology offers the advantages of various material applicability and high flexibility for fabricating filamentary interconnects. The printing resolution is, however, highly dependent on the needle size. A micro-printing method was proposed based on fluid drawing to fabricate freestanding 3D conductive structures. The delicate structure is drawn out under the tension when printing. The printing material is a high-viscosity ink composed of silver nanoparticles (AgNPs) and polyvinylpyrrolidone (PVP). The viscosity is controlled by evaporating the ink’s solvent for drawing prints. This unique printing method utilizes a single needle, controlled by precise air pressure and speed, to construct 3D filamentary structures with varied wire widths. The 3D conductive structures exhibit superior structural retention and enhanced conductivity by thermal treatment. The drawing printing method has been successfully implemented on flexible circuits, including light-emitting diode (LED) arrays, thermal imaging displays, and multivibrator circuits. This work establishes a novel paradigm for flexible electronics manufacturing through fluid-drawing printing, achieving unprecedented customization and compatibility in fabricating 3D interconnects.